Moderate volume of sprint bouts does not induce muscle damage in well-trained athletes - Machado, L. F.; Farinha, J.; Fagundes, A.; Voser, R.; Reischak-Oliveira, A.; Setuain, I.; Izquierdo, M.; Pinto, R. S.; Cadore, E. L. (Journal of Bodywork and Movement Therapies, 2020)
Understanding the recovery in response to different sprint protocols is important for optimizing neuromuscular gains and organizing training sessions in sports. The current study aimed to investigate acute neuromuscular changes following a moderate volume of sprint protocols with and without change-of-direction. Methods: 26 well-trained male collegiate athletes from different sports were randomly allocated into straight-line group (SLG) or change-of-direction group (CODG). The protocols were 1 x 15 repetitions of 20-meter sprints in line (SLG) or with two changes in each repetition (CODG). Knee extension maximal and explosive strength, jump performance, serum creatine kinase, and quadriceps and hamstrings echo intensity were collected pre-, post- 0, 24, 48, and 72 hours post-exercise. Results: There were no significant changes in any of the variables at any time point after the exercise protocols in comparison with pre-exercise values (p>0.05). Conclusins: Therefore, the present study suggests that sprint training with moderate volume with or without change-of-direction does not induce neuromuscular or physiological changes during 72 hours post-exercise. This information is especially important for sports staff in order to optimize training prescription and frequency.